Aplikasi Alat Geolistrik Tahanan Jenis untuk Mendeteksi Ketersediaan Air Tawar bagi Masyarakat Suli-Suli Kabupaten Maros - Sulistiawaty Sulistiawaty; Pariabti Palloan; Muhammad Arsyad; Vistarani Arini Tiwow; Andi Bida Purnamasari (JKM: Jurnal Kemitraan Masyarakat, 2025)
Clean fresh water is one of the basic needs that is difficult to obtain by the Suli-suli community, so the local community collects rainwater or buys it to get fresh water. . The dominant service location is close to the coast and Karst mountain so that the local community is increasingly difficult to obtain fresh water. So to help the Suli-suli community obtain fresh water, a groundwater search service was carried out. The service provider conducted measurements using a geoelectric resistivity tool with the Wenner-Schlumberger method approach with a span of 147 m per measurement path. The results obtained that the presence of groundwater was obtained at a depth of 2-15 meters. However, there are several points where there is also brackish water, this is because the service location is close to the coast so that seawater intrusion occurs which forms brackish water, but after a depth of 5 meters down the brackish water is no longer visible. From the results of this service, it is hoped that it will be a reference for the community in finding and making freshwater wells, in order to meet the need for clean water.